Accountability for Village Fund Allocation Management: Value for Money Performance Measurement as Moderation - Masdi Masdi; Taufeni Taufik; Yesi Mutia Basri (Wahana Riset Akuntansi, 2023)
Purpose–This study wants to look at how organizational commitment and internal control systems affect the accountability of village fund allocation management, with value-for-money-based performance measures as a moderating variable.Design/methodology/approach– All ten villages in Sungai Lala District, Indragiri Hulu Regency, were included in this study. This study used a saturated sample technique, in which all populations were sampled, namely ten villages. Ten respondents were taken from each village, so the number of respondents in this study was 100 with 93 responses used for analysis. The relationship between variables was analyzed using SEM with Smart PLSFindings– Results indicate that organizational commitment and internal control mechanisms have a favorable and significant impact on village budget allocation management accountability. Value-for-money-based performance measures can moderate the influence of organizational commitment.Originality/values– This study uses performance measurement with value for money as moderation. Performance measurement is essential to increase commitment and strengthen internal control to realize accountability for village fund allocation management.Research limitations/implications– This research has the limitation that the village government only carried it out in the Sungai Lala sub-district, Indragiri Hulu Regency. This research contributes to the village government's need to strengthen commitment, internal control systems, and performance measurement with value for money.